Determinants of Purchase Intention for Used Electric Vehicles in Indonesia: An Extended Theory of Planned Behavior Approach - Rizky Chandraditya Effendi; Imam Salehudin (Borong Newinera Publisher, 2026)
The volatile Indonesian used EV market is characterized by high consumer uncertainty due to aggressive new EV price wars, necessitating an understanding of the key factors driving purchase intention. This study analyzed the determinant factors influencing consumer purchase intention toward used EVs in Indonesia using an Extended Theory of Planned Behavior (TPB) framework by examining five individual motivational Attitude dimensions, Attitude, Perceived Behavioral Control (PBC), Subjective Norms, Past Purchase Experience, electronic Word-of-Mouth (e-WOM), and Willingness to Pay (WTP). A quantitative survey of 426 valid Indonesian respondents was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Research indicate that Economic Motivation is the sole significant antecedent to Attitude strongly dominating sustainable and ethical motivations, Perceived Behavioral Control (PBC) emerged as the strongest predictor of Purchase Intention underscoring consumer technical risk aversion, Attitude exhibited a marginal negative effect on Purchase Intention, suggesting that technical risk concerns outweigh positive sentiment, Purchase Intention significantly drives both e-WOM and WTP, confirming its central role in the adoption ecosystem. The conclusion is that used EV adoption in Indonesia is driven by rational economic calculation and technical confidence, rather than environmental values. Managerially, the necessity for standardized battery health certification is highlighted to enhance consumer Perceived Behavioral Control (PBC). This research offers novelty by integrating five specific motivational dimensions into an extended TPB framework to analyze purchase intention, e-WOM, and WTP within the unique and volatile Indonesian used EV market, particularly highlighting the dominant role of Economic Motivation and PBC in a developing market with high price volatility.